AN ANALYSIS OF STUDENTS’ ENGLISH COMPETENCE (TOEFL EQUIVALENT) AT RIAU UNIVERSITY PEKANBARU - Ras , Fakhri (JEE (Journal of English Education), 2016)
This study aims to investigate the competence of students’ English language (TOEFL Equivalent) at Riau University Pekanbaru and the factors associated with (gender, parents economic background, and majors in high school). The research Population is Riau University students who take the TOEFL Prediction in 2015/2016 - approximately 7,000, - students. The samples were taken at 5% of the total population of 350 students. TOEFL Prediction - compiled by UP2B Universitas Riau - used to collect data. The results of this study are as follows: a) the average score of TOEFL Equivalent Riau University students are 372, b) the averag scores of female students slightly higher (374) than the average scores of male students, c) the average score of economic students parents medium slightly higher (376) than the economics student parents low, and d) the average score of students whose background natural science (IPA) also slightly higher (378) than the students background knowledge social knowledge (IPS). The implications of the findings of this study are students need training intensive TOEFL Prediction on aspects of listening (mini - talk), reading comprehension (reading comprehension - the main idea and supporting ideas), and grammar / writing expression (sentence error).